2004
DOI: 10.1139/z04-116
|View full text |Cite
|
Sign up to set email alerts
|

Season variation in nutrient composition of Alaskan walleye pollock

Abstract: A popular hypothesis for the noted steady decline in the population of Steller sea lions, Eumetopias jubatus (Schreber, 1776), in the regions from Prince William Sound through the Aleutian Islands relates to their nutritional status. Sea lion diets appear to have shifted from primarily small schooling fatty fishes to low-fat fish such as walleye pollock, Theragra chalcogramma (Pallas, 1814). We examined the seasonal changes in proximate nutrients of pollock collected in the Bering Sea. Mean energy density (dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 23 publications
0
40
0
Order By: Relevance
“…Fatty acids were methylated with boron trifluoride (BF 3 ) in methanol (Kitts et al, 2004). The fatty acid methyl esters (FAME) were analyzed by gas chromatograph (Agilent 6890, USA) equipped with flame ionization detector and an auto injector (Agilent 7683, USA).…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…Fatty acids were methylated with boron trifluoride (BF 3 ) in methanol (Kitts et al, 2004). The fatty acid methyl esters (FAME) were analyzed by gas chromatograph (Agilent 6890, USA) equipped with flame ionization detector and an auto injector (Agilent 7683, USA).…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…The fatty acid composition might be related to the changes in nutritional habits of the fish. Kitts et al (2004) reported that the fatty acid composition and lipid contents of fish were affected by the species, sex, age, water temperature, degree of pollution, nutritional condition, seasonal variation and fish origin. The nutritional benefits of fish are mainly due to the content of high quality protein and high content of two kinds of ω-3 polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl pentadecanoate (10-100 g) from a standard solution (5 mg/ml) was added to each tube as the internal standard, except that pentadecane (10 g) was used as the internal standard for hydrocarbons analysis. FAME was prepared by heating with silica gel for 30 min at 80 ºC in BF 3 /methanol (Kitts et al, 2004). The FAME was quantified by gas chromatography (GC, 14B GC Shimadzu) equipped with a hydrogen flame ionization detector (FID) at 350 C and a polar capillary column (ULBO HE-SS-10 for FAME, fused silica WCOT [no.…”
Section: Lipid Analysismentioning
confidence: 99%